2017
DOI: 10.1155/2017/4153076
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Consequences of Dopamine Depletion-Induced Attenuation of the Spinophilin/Neurofilament Medium Interaction

Abstract: Signaling changes that occur in the striatum following the loss of dopamine neurons in the Parkinson disease (PD) are poorly understood. While increases in the activity of kinases and decreases in the activity of phosphatases have been observed, the specific consequences of these changes are less well understood. Phosphatases, such as protein phosphatase 1 (PP1), are highly promiscuous and obtain substrate selectivity via targeting proteins. Spinophilin is the major PP1-targeting protein enriched in the postsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 60 publications
(93 reference statements)
2
44
1
Order By: Relevance
“…We measured CK2 activity indirectly by using an antibody against the phospho-CK2 substrate (motif pS/pTDXE) to measure the amount of phosphorylated CK2 substrates. This method is widely used in literature to measure kinase activity, such as activity of the following kinases CK2 [ 16 , 49 , 50 , 51 , 52 ], AMPK [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], AMT/ATR [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], PKA [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and PKC [ 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Both CK2 knockdown and CX-4945 treatment inhibited the proliferation of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…We measured CK2 activity indirectly by using an antibody against the phospho-CK2 substrate (motif pS/pTDXE) to measure the amount of phosphorylated CK2 substrates. This method is widely used in literature to measure kinase activity, such as activity of the following kinases CK2 [ 16 , 49 , 50 , 51 , 52 ], AMPK [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], AMT/ATR [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], PKA [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and PKC [ 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Both CK2 knockdown and CX-4945 treatment inhibited the proliferation of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…We created constructs that encoded HA-tagged human spinophilin [62] along with a P2A sequence and a far-red fluorescent protein (mNeptune3 [71]). Mice were generated from these constructs by the Vanderbilt Transgenic Mouse/ESC Shared Resource (see methods).…”
Section: Resultsmentioning
confidence: 99%
“…All animal studies were performed in accordance with the Guide for the Care and Use of Laboratory Animals as disseminated by the U.S. National Institutes of Health and were approved by Indiana University-Purdue University School of Science Animal Care and Use Committees (Approval #SC270R). A human, HA-tagged spinophilin construct [62] containing a P2A sequence and the mNeptune 3 protein were assembled into the pBigT vector between the ClaI and SacI restriction sites (Figure 1A). Gene files were assembled in SnapGene (GSL Biotech, Chicago, IL, USA) or Vector NTI (ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the catalytic subunit of PKA (PKAc) in HEK293 cells increases spinophilin and GluN2B interaction PKA phosphorylates both spinophilin and NMDA receptor subunits (Hsieh-Wilson et al 2003;Murphy et al 2014) and our previous studies have found that PKA can regulate spinophilin interactions (Hiday et al 2017). V5-tagged GluN2B Tail and HA-tagged spinophilin were co-expressed in HEK293 cells alone or alongside a Myc-tagged form of the catalytic subunit of protein kinase A (PKAc).…”
Section: Resultsmentioning
confidence: 95%